Historical projection of Francisco Suárez: Xavier Zubiri - Monserrat, Javier (Pensamiento. Revista de Investigación e Información Filosófica, 2018)
The epistemological and metaphysical work of Francisco Suárez represented an important change in scholastic philosophy. Therefore it has been denominated like Second Scholastic. In fact, more than a «change» or «reform» of Thomism, it is a real alternative. In Suarez have their echo both nominalism and modern science. These points of reference make us understand why Suarez said what he said. Pure Thomism assumed a «hard» interpretation of Greek dualism and this had given rise to the theory of the prevalence of the universal in the cognitive process. Nominalism and modern science did not go along this line. Suarez also changed perspective, making it more conformable with his time, by reconstructing the process of knowledge from the epistemological theory of the prevalence of the singular over the universal in the cognitive process. During the following centuries, the work of Suárez was an effective alternative to the pure Thomism, mainly by the educational work of the Jesuits. For this reason, the philosophical style of Suárez marked a line of philosophical presence in Spain. We believe that it is possible to speak of a constant Spanish philosophical style that picks up the great lines of Suárez. This way of thinking has been projected, or has fructified, in the twentieth century, in authors like Amor Ruibal and Zubiri. In this article we will show the connection between the epistemology of Suárez and that of Zubiri.
Keywords: Suárez; Zubiri; theory of knowledge; singular; universal; cognitive process